2022
DOI: 10.1002/smll.202106707
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Electron Redistribution of Hydrangea‐like NiO@Ni2P Heterogeneous Microspheres with Dual‐Phase Synergy for High‐Performance Lithium–Oxygen Battery

Abstract: ultimately increasing the charge transfer resistance. [8] During the OER process, the insulated Li 2 O 2 can only be decomposed at high overpotential, which can trigger severe parasitic reactions. [9][10][11] Therefore, exploring efficient bifunctional electrocatalysts and understanding the formation and decomposition mechanism of Li 2 O 2 is of great significance for effectively reducing ORR and OER overpotential and improving the electrochemical performance of LOBs.Currently, two types of mechanisms (solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…Notably, the Ni 2p XPS of Ni 2 P@NiO/NiF deconvoluted into two doublets along with their shake-up satellites peaks located at 853.5 eV and 871.7 eV, originating at the Ni 2+ component and shifted to a binding energy range by 0.38 eV and 0.48 eV that related to the NiO/NiF catalyst ( Figure 4 D). The above observed shift was mainly ascribed to the binding of the O, P, and Ni elements on Ni 2 P@NiO, which clearly confirmed the insertion of the Ni 2 P nanoparticles on the NiO nanosheet structure [ 51 , 52 ]. The O 1 s XPS of the Ni 2 P@NiO/NiF-40 and NiO/NiF samples are displayed in Figure 4 D. The O 1 s deconvoluted into three components at 528.9, 530.7, and 531.5 eV, corresponding to the lattice oxygen, the hydroxyl component, and the structurally adsorbed water, respectively.…”
Section: Resultsmentioning
confidence: 80%
“…Notably, the Ni 2p XPS of Ni 2 P@NiO/NiF deconvoluted into two doublets along with their shake-up satellites peaks located at 853.5 eV and 871.7 eV, originating at the Ni 2+ component and shifted to a binding energy range by 0.38 eV and 0.48 eV that related to the NiO/NiF catalyst ( Figure 4 D). The above observed shift was mainly ascribed to the binding of the O, P, and Ni elements on Ni 2 P@NiO, which clearly confirmed the insertion of the Ni 2 P nanoparticles on the NiO nanosheet structure [ 51 , 52 ]. The O 1 s XPS of the Ni 2 P@NiO/NiF-40 and NiO/NiF samples are displayed in Figure 4 D. The O 1 s deconvoluted into three components at 528.9, 530.7, and 531.5 eV, corresponding to the lattice oxygen, the hydroxyl component, and the structurally adsorbed water, respectively.…”
Section: Resultsmentioning
confidence: 80%
“…2e). Furthermore, for Ni species, four peaks from the Ni 2p spectrum locating at binding energies of 857.88, 863.44, 875.34 and 881.4 eV corresponded to Ni 2p 3/2 regions, satellite peak, Ni 2p 1/2 region and satellite peak, respectively 45 (Fig. 2f).…”
Section: Resultsmentioning
confidence: 96%
“…Under such conditions, the poor contact between the cathode and Li 2 O 2 made the electrocatalytic performance unsatisfactory, leading to residual discharge products and poor electrochemical performance. [79][80][81] Electron localization function (ELF) calculations were performed for different catalysts to investigate the P doping effect on electron distribution properties, and color scales and corresponding ELF values are listed on the right, as shown in the dashed boxes. It can be clearly observed that the introduction of P atoms resulted in charge redistribution to form a highly reactive electron-like gas region with high reactivity, which contributed to the rapid transport of carriers and efficient adsorption of adsorbates for the OER and ORR.…”
Section: Resultsmentioning
confidence: 99%